The Island in Conceição Lima’s Poetry - Joana Castaño (Journal of Lusophone Studies, 2016)
In this article, I discuss the poetry of the San Tomean poet Conceição Lima. In particular, I focus on her treatment of the island as both an abtract form and an empirical reality. I offer readings of a broad cross-section of Lima’s work, and I argue that for her the island ultimately comes to represent home.